2020
DOI: 10.2147/cmar.s260695
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predicting Individual Prognosis and Grade of Patients with Glioma Based on Preoperative Eosinophil and Neutrophil-to-Lymphocyte Ratio</p>

Abstract: Purpose: Eosinophils are proven to play a role in the prognosis of some malignant-tumors. The prognostic value of eosinophils in glioma patients is, however, scarcely reported. The authors of this article have designed a novel prognostic indicator based on eosinophils and the neutrophil-to-lymphocyte ratio (NLR), named ENS, to predict the survival of patients with glioma. Methods: A retrospective study was conducted on 217 glioma patients. The cutoff values for eosinophil, NLR, and other clinical variables wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…There are also some significant progress in the basic research, and comprehensive therapy of glioma has been made in recent years. However, the prognosis of patients with glioma has not been significantly improved as glioma induces an immune infiltrating environment [5,6]. In general, poor glioma prognosis shows a high rate of recurrence after treatment [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…There are also some significant progress in the basic research, and comprehensive therapy of glioma has been made in recent years. However, the prognosis of patients with glioma has not been significantly improved as glioma induces an immune infiltrating environment [5,6]. In general, poor glioma prognosis shows a high rate of recurrence after treatment [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Relevant to this statement, empirically, remarkably fully 13 independent studies just between 2018 and 2020 reported the same findings-that a higher neutrophil to lymphocyte ratio-a relative or absolute neutrophilia-correlated with shorter survival in GB [66][67][68][69][70][71][72][73][74][75][76][77][78]. Few parameters in any cancer have been so oft confirmed.…”
Section: Dapsone Gb and Neutrophilsmentioning
confidence: 85%
“…The incidence of LGG is increasing worldwide (Zhang et al, 2020). LGG patients have a relatively favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%